An individually adjusted endurance test reveals differences in physical fitness between young and old Beagles - Willen, Maray; Lorke, Malin; Wefstaedt, Patrick; Lucas, Karin; Nolte, Ingo (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective Aim was to establish an individually adapted endurance test for dogs on a treadmill, which takes the individual‘s physical condition into account. To check the applicability of the test, two age groups of clinically healthy beagles were examined.Methods A total of 10 clinically healthy Beagles were enrolled and divided in a younger (1–3 years, n = 5) and older group (> 8 years, n = 5). The individual comfort gait speed of each dog was determined on a treadmill with integrated force plates. A maximal time of 20 minutes at trot was set for the endurance test. The test was terminated prematurely if the dog showed signs of fatigue (massive panting, unwillingness to move further). Blood samples were taken at general examination (G), prior to (B) and post exercise (P) for determination of lactate level (LL), oxygen and carbon dioxide partial pressure (pO2, pCO2), bicarbonate (HCO3–), base excess (BE) and pH. On each occasion (G, B, P) heart rate (HR) and respiratory rate (RR) were recorded. Additionally, vertical ground reaction forces (Fz) were analysed.Results The older dogs (age: 10.4 ± 0.89 years) completed the test with less speed and duration compared to the younger dogs (age: 2.4 ± 0.89 years), which managed to complete the maximum time. Lactate levels in the older dogs were higher than in the younger dogs at all timepoints of examination. Contrary to the younger dogs, there was no significant increase in the heart rate of the older dogs. Ground reaction forces were not significantly different between the groups.Conclusion and clinical relevance Whereas standardised endurance tests allow for the comparison of fitness levels between dogs, an individually adjusted endurance test aims at objectively determining the physical fitness of the single dog taking into account its individual performance. Such a test allows to examine the individual performance development over time and to evaluate medicinal therapies or dietary measures, e. g. in aging dogs. HR, RR, LL, blood gases (pCO2, pO2) and acid-base metabolism (HCO3–, BE, pH) were found to be appropriate parameters for determining the physical capacity of the dogs during endurance tests as these parameters change under physical stress and are indicative for the onset of fatigue.
Keywords: Body condition; lactate; treadmill; dog; gait analysis